You are on page 1of 1

For the DE of the form

dy + f ( x) y = g ( x), dx

f ( x ) dx We will multiply both sides by an integrating factor given by e , such that the above becomes

f ( x ) dx

f ( x ) dx f ( x ) dx f ( x ) dx dy + f ( x )e y = e g ( x) = h( x) , where h( x) = e g ( x) dx

This is equivalent through reduction (by the product rule for the LHS) to

d f ( x ) dx ye = h( x) dx
Integrating both sides wrt x gives ye
f ( x ) dx

= h( x)dx + C

f ( x ) dx Therefore, the general solution is y = e

[ h( x)dx + C ]

(shown)